Efektivitas Tata Tertib Madrasah Dalam Kedisiplinan Santri Di MA PPPI Miftahussalam Banyumas - Alfansyah, Muhamad Zaki; Setianingsih, Cahyani Ayu; Setyaningsih, Rahma Pangestu; Makhful (CV. Amerta Media, 2024)
This research aims to discuss the effectiveness of madrasa rules and regulations in creating discipline for MA PPPI Miftahussalam Banyumas students. Madrasah rules and regulations are the rules set by the madrasah to create an orderly and disciplined learning environment. Effective implementation of madrasa rules and regulations at MA PPPI Miftahussalam Banyumas involves steps such as introducing the rules to new students and continuous monitoring of their implementation. In this article, it is explained that effective madrasa rules and regulations have a positive impact on student discipline, such as students being more focused on learning and respecting time and the learning process. In conclusion, effective madrasa regulations are very important in creating discipline for MA PPPI Miftahussalam Banyumas students. Keywords: effectiveness; discipline; oreder; madrasah Penelitian ini bertujuan untuk membahas tentang efektivitas tata tertib madrasah dalam menciptakan kedisiplinan santri MA PPPI Miftahussalam Banyumas. Tata tertib madrasah merupakan aturan yang ditetapkan oleh madrasah untuk menciptakan lingkungan belajar yang tertib dan disiplin. Penerapan tata tertib madrasah yang efektif di MA PPPI Miftahussalam Banyumas melibatkan langkah-langkah seperti pengenalan tata tertib kepada santri baru dan pengawasan kontinu terhadap penerapannya. Dalam artikel ini dijelaskan bahwa tata tertib madrasah yang efektif memiliki dampak positif terhadap kedisiplinan santri, seperti santri yang lebih fokus pada pembelajaran dan menghargai waktu serta proses pembelajaran. Kesimpulannya, tata tertib madrasah yang efektif sangat penting dalam menciptakan kedisiplinan santri MA PPPI Miftahussalam Banyumas. Kata kunci : efektivitas; kedisiplinan; tata tertib; madrasah